International Film Festivals as Indicators of Trends in Film Production - Permiakova, Sofia; Michalik, Pavel, 1972-; Svoboda, Jaroslav; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2024)
This thesis explores the influence of sociocultural or political agendas on the success of films at international film festivals and their impact on global film production trends. By analysing films awarded at major festivals over the past decade, this study tests two hypotheses: films that are in line with liberal values are more likely to win awards, and such recognition significantly influences global film production. Employing a mix of quantitative and qualitative methods, including thematic analysis and statistical tests, the research examines the prevalence and effects of themes aligned with liberal values in films. The findings indicate that while sociocultural and political themes are common in award-winning films, their presence does not statistically increase the likelihood of winning. Additionally, the themes of award-winning films do not necessarily dictate the thematic direction of global film production. This study contributes to the understanding of the cultural role of film festivals, suggesting that while they showcase relevant sociocultural issues, they do not necessarily determine production trends.
Vedoucí práce: Pavel Michalik
Bakalářská práce (Bc.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2025
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2025
Způsob přístupu: Internet
Keywords: multimédia v ekonomické praxi [obor bakal. práce]; bakalářské práce; bachelor's theses